DEVELOPMENT OF AMORPHOUS BINARY AND TERNARY SOLID DISPERSIONS OF NATEGLINIDE FOR IMPROVED SOLUBILITY AND DISSOLUTION - TIWARI, SHRADHA S.; WADHER, SHAILESH J.; GATTANI, SURENDRA G. (International Journal of Applied Pharmaceutics, 2020)
Objective: Nateglinide is a commonly used oral hypoglycemic, biopharmaceutical classification system Class II drug, which shows relatively poor water solubility and variable bioavailability. The objective of the present investigation was to develop the binary and ternary solid dispersions of nateglinide for improved solubility and dissolution. Methods: Nateglinide solid dispersions were prepared by a common solvent evaporation method. Polymers like soluplus, kolliphor P188, sylloid 244FP, gelucire 48/16, affinisol (HPMCAS), HPβCD, βCD were used in different combinations. The physicochemical characterization of the optimized ternary dispersion was studied by using FT-IR, DSC, and PXRD. Solubility and dissolution behavior of all dispersions were studied. Result: From all prepared ternary solid dispersions, nateglinide dissolution was significantly faster than pure nateglinide. With ternary solid dispersion of NTG, soluplus and kolliphor P188 there was a big improvement in solubility and dissolution. This combination enhanced the solubility of NTG by 23 folds. Another ternary dispersion of NTG with soluplus and gelucire 48/16 enhanced solubility by 25 fold. Conclusion: Ternary solid dispersion found superior over binary dispersions. For the ternary dispersions, showing the best solubility, tablets were prepared. Dissolution and drug release from the formulated tablet was as good as a marketed product.